Investigating the relationship between experience, well-being, and loyalty: A study of wellness tourists - Ramjit Singh; Parikshat Singh Manhas; Mudasir Ahmad Mir; Joana A. Quintela (Administrative Sciences, 2022)
The present research aims to determine the relationship between the construct of autonomy, intrinsic motivation, and tourist experience, as well as loyalty in the context of wellness and spa tourism. The exploratory-descriptive design was adopted in the present research. A research instrument was developed based on previous literature and was tested for a pilot study to check validity and reliability. A purposive sampling technique was used to collect the data from tourists who have gained spa experience. A total of 264 usable responses were received after distributing 400 questionnaires. The data were screened, processed, and analyzed using the SPSS 22.0 and Smart-PLS 2.0. The investigation showed that intrinsic motivation, autonomy, and experience positively impact positive emotions and life satisfaction. Besides, it also supported that positive emotions, experience, and life Satisfaction lead to loyalty. Furthermore, the present study tested the mediating role of experience, positive emotions, and life satisfaction; it was also found that experience mediates the relationship between autonomy, positive emotions, and life satisfaction. Positive emotions and life satisfaction were mediators in the relationship between experience and loyalty. Finally, the findings showed that destination images moderated the relationship between experience, positive emotions, and life satisfaction. The results of this investigation can be helpful for both the research community and marketers interested in investigating the well-being of tourists and destination loyalty.
Keywords: 350; life satisfaction; loyalty; mediation; positive emotions; spa-wellness; tourist experience